Photoperiod and Temperature as Dominant Environmental Drivers Triggering Plant Phenological Development of American Ginseng Along With Its Quality Formation - Chen, Tingting; Wang, Liqin; Wang, Hongtao; Jiang, Sheng; Zhou, San (Frontiers in Earth Science, 2022)
American ginseng [Panax quinquefolius L.] has been cultivated in many locations of China, we have noticed that its phenological performance as well as quality characteristics varied from location to location. However, the exogenous factors driving this process are still poorly understood, and this reduces the successful introduction in American ginseng for quality ensuring. Here, we conducted field and cabinet experiments to explore the relationship among environmental factors, phenological development and ginsenosides accumulation in American ginseng. In the field experiments, we found that American ginseng from different original locations showed different phenological rhythm and different ginsenosides accumulation. Especially, those from higher latitude locations (Wuchang as an example, 44.55°N) presented delayed spring phenology and advanced autumn phenology, but higher ginsenosides contents along with higher gene expression levels of ginsenosides biosynthesis than those from lower latitude locations (Wendeng as an example, 37.23°N). Data analysis indicated that the phenological rhythm of American ginseng is closely related to the seasonal change of environmental factors, especially winter chilling duration, spring warming and autumn day-length shortening. In the cabinet experiments, results further proved that temperature interacting with photoperiod play a decisive role in the phenological development and ginsenosides accumulation of American ginseng in the absence of water and nutrient limitation. Both field and cabinet experiments indicated that that sufficient winter cold exposure coupling to spring long day-length photoperiod are beneficial environmental factor to normal spring phenology development while shortening autumn day-length coupling to autumn cooling are beneficial environmental factor to normal autumn phenology development of American ginseng. Results also indicated that insufficient cold exposure and unsuitable day-length photoperiod are detrimental factors to both spring and autumn phenology, and not good for ginsenosides accumulation in American ginseng. The understanding of the environmental factors influencing on the phenological development along with ginsenosides accumulation can provide guidance for predicting suitable cultivation locations and improving planting technique for high-yield and good-quality of American ginseng.